La aceleración como estrategia educativa para alumnos de alta capacidad académica. Concepto, modalidades y evaluación de resultados - Repáraz Abaitua, Charo; Peralta López, María Felisa; Tourón, Javier (Revista Española de Pedagogía, 2018)
This paper is focused on the academic acceleration as one of the most adequate option to reach an optimal match between the special educational needs of academic talented students and the curriculum they have to follow. Very often we see that the curriculum that schools offer to the regular students is not challenging enough for those children who can reason extremely well in some academic areas (i. e. verbal and mathematics). Most of the time this can be harmful to these kind of students sometimes causing them to develop poor study and work habits and become lazy intellectually. The educational system must offer different kinds of accelerated options permitting those highly able students to be adequately challenged and stimulated. This work revises the most recent and meaningful studies in this field, showing the effects of different kinds of academic acceleration. The major concern of those people who are detractors of this academic option is the possible problems of social or emotional adjustment caused by the academic acceleration, but this argument can not be supported on the research findings. Moreover, research clearly states that when academic acceleration is applied to carefully selected students it produces more benefits than negative effects and constitutes one of the most adequate ways to nurture and develop the academic talent.
Keywords: estrategia educativa; alumnos; alta capacidad académica; Revista Española de Pedagogía